Horticultural activities can achieve the same affect improvement effect of green exercise: A randomized field controlled trial - Tao, Meng; Lu, Li; Gao, Jingchuan; He, Xiaolong (Frontiers in Psychology, 2022)
Objectives: This study compared the affect improvement between horticultural activities with the same intensity and green exercise and that with or without green plants to verify the value of horticultural activities and green exercise in improving human affect and the importance of green plants.Methods: A total of 160 subjects aged 18–26 years (average age 22.5 years) were recruited and randomly divided into a control group, a horticultural activity group with green plants, a horticultural activity group without green plants, and a green exercise group. Demographics, sociological variables, and daily physical activity levels were investigated. After finishing the preparation work, the subjects sat quietly for 8 minutes before the pre-test. The horticultural group completed 20 minutes of horticultural activities [8 minutes of digging (40%*HRR+RHR) + 8 minutes of transplantation (50%*HRR+RHR) + 4 minutes of watering (30%*HRR+RHR)]. The group returned to a calm state (no less than 20 minutes) for the post-test. The green exercise group completed a 20-minute power bike ride. The activity intensity and activity time of the green exercise group were determined according to the activity intensity and time of the horticultural group. Dependent variables were collected, including blood pressure, positive/negative emotions, heart rate variability (RMSSD, SDNN, and LF/HF), and controlled covariate environmental parameters (field temperature, humidity, and noise).Results: (1) A significant difference was observed in the improvement effect except for negative emotion between the green horticultural activity group and the green exercise group (F=3.310;ɳp2=0.046;p=0.037). No significant difference was observed in other emotion indicators. (2) In the same pattern of with and without green plant horticultural activity group, the green plant horticultural activity group had a better effect on the improvement of affect, and the two groups had a better negative affect (F=3.310;ɳp2=0.046;p=0.037), SDNN index of heart rate variability (F=1.035; ɳp2=0.015;p=0.039), and RMSSD index (F=2.225;ɳp2=0.032;p=0.014), and no significant difference was observed in the improvement effect of other affect indicators between the two groups.Conclusions: Having green horticulture can give the same intensity as green exercise and affect improvement. Under the same pattern of horticultural activities, green plants are the key factor in improving the affect of horticultural activities.